2018
DOI: 10.1371/journal.pone.0204285
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after stroke attributable to baseline factors—The PROSpective Cohort with Incident Stroke (PROSCIS)

Abstract: BackgroundThe impact of risk factors on poor outcome after ischemic stroke is well known, but estimating the amount of poor outcome attributable to single factors is challenging in presence of multimorbidity. We aim to compare population attributable risk estimates obtained from different statistical approaches regarding their consistency. We use a real-life data set from the PROSCIS study to identify predictors for mortality and functional impairment one year after first-ever ischemic stroke and quantify thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 31 publications
0
35
1
Order By: Relevance
“…Epidemiologic data regarding stroke recurrence among younger patients are limited. In addition, several factors including older age [44], hypertension [45], diabetes [46,47], and current smoking [45] are associated with stroke death. Appelros et al showed that old age, atrial fibrillation, stroke severity, and dementia were predictors of poor outcomes including death within one-year after stroke [48].…”
Section: Stroke Risk Factors and Predictors Of Poor Outcomesmentioning
confidence: 99%
“…Epidemiologic data regarding stroke recurrence among younger patients are limited. In addition, several factors including older age [44], hypertension [45], diabetes [46,47], and current smoking [45] are associated with stroke death. Appelros et al showed that old age, atrial fibrillation, stroke severity, and dementia were predictors of poor outcomes including death within one-year after stroke [48].…”
Section: Stroke Risk Factors and Predictors Of Poor Outcomesmentioning
confidence: 99%
“…[ 17 ] Low education is related to poor stroke outcome also. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Dementia occurs in approximately 10% and 34.4% of first-ever mild and severe stroke survivors, respectively, within the first year poststroke, and in around 30% of stroke survivors after recurrent stroke. 39,70,71 In fact, evidence suggests that those with higher cognitive reserve (higher educational attainment) are at a decreased risk of developing dementia following stroke and/or transient ischemic attack (see Mirza et al 71 and Malsch et al 72 ). It should also be mentioned that brain reserve might also be a suitable target for intervention.…”
Section: The Significance Of Cognitive Reserve For Stroke Impairment mentioning
confidence: 99%